Aqueous Solution Chemistry of Ammonium Cation in the Auger Time Window - Hollas, Daniel; Pohl, Marvin N; Seidel, Robert; Aziz, Emad F; Slavíček, Petr; Winter, Bernd (Scientific reports, 2017)
We report on chemical reactions triggered by core-level ionization of ammonium ([Formula: see text]) cation in aqueous solution. Based on a combination of photoemission experiments from a liquid microjet and high-level ab initio simulations, we identified simultaneous single and double proton transfer occurring on a very short timescale spanned by the Auger-decay lifetime. Molecular dynamics simulations indicate that the proton transfer to a neighboring water molecule leads to essentially complete formation of H3O+ (aq) and core-ionized ammonia [Formula: see text](aq) within the ~7 fs lifetime of the nitrogen 1s core hole. A second proton transfer leads to a transient structure with the proton shared between the remaining NH2 moiety and another water molecule in the hydration shell. These ultrafast proton transfers are stimulated by very strong hydrogen bonds between the ammonium cation and water. Experimentally, the proton transfer dynamics is identified from an emerging signal at the high-kinetic energy side of the Auger-electron spectrum in analogy to observations made for other hydrogen-bonded aqueous solutions. The present study represents the most pronounced charge separation observed upon core ionization in liquids so far.